Discovery of Novel Bacterial Cell-Penetrating Phylloseptins in Defensive Skin Secretions of the South American Hylid Frogs, Phyllomedusa duellmani and Phyllomedusa coelestis - Yang, Nan (Toxins (Basel), 2016)
Phylloseptin (PS) peptides, derived from South American hylid frogs (subfamily Phyllomedusinae), have been found to have broad-spectrum antimicrobial activities and relatively low haemolytic activities. Although PS peptides have been identified from several well-known and widely-distributed species of the Phyllomedusinae, there remains merit in their study in additional, more obscure and specialised members of this taxon. Here, we report the discovery of two novel PS peptides, named PS-Du and PS-Co, which were respectively identified for the first time and isolated from the skin secretions of Phyllomedusa duellmani and Phyllomedusa coelestis. Their encoding cDNAs were cloned, from which it was possible to deduce the entire primary structures of their biosynthetic precursors. Reversed-phase high-performance liquid chromatography (RP-HPLC) and tandem mass spectrometry (MS/MS) analyses were employed to isolate and structurally-characterise respective encoded PS peptides from skin secretions. The peptides had molecular masses of 2049.7 Da (PS-Du) and 1972.8 Da (PS-Co). They shared typical N-terminal sequences and C-terminal amidation with other known phylloseptins. The two peptides exhibited growth inhibitory activity against E. coli (NCTC 10418), as a standard Gram-negative bacterium, S. aureus (NCTC 10788), as a standard Gram-positive bacterium and C. albicans (NCPF 1467), as a standard pathogenic yeast, all as planktonic cultures. Moreover, both peptides demonstrated the capability of eliminating S. aureus biofilm.